p-variation of Ornstein–Uhlenbeck type processes - Manstavičius, Martynas (Lietuvos matematikos rinkinys, 2007)
The p-variation of sample paths of Ornstein–Uhlenbeck type processes is investigated. It is shown that the p-variation index of such a process is the same as the p-variation index of the driving Lévy process, provided this process is of unbounded total variation.
Keywords: positive diffusion; weak second-order a pproximation; CIR equation; CKLS equation